Investigating The Power Quality Improvement On Laboratories Equipment Base On Voltage And Current Analysis - Ab Hadi, Nik Azran; Mohd Annuar, Khalil Azha; Mohammad Azmi, Mohamad Azim; Salleh, Azahari; Mohd Ab Halim, Mohd Firdaus; Abd Rashid, Wan Norhisyam; Mohd Noh, Mohd Syahrin Amri (Penerbit Universiti,UTeM, 2018)
After four years the Faculty of Engineering Technology was opened,the equipment/computer have installed for doing the experiment in laboratories beginning faulty.The technician was informed by the vendors that the equipment/computer was break down due to power supply. The vendor told that it was not occurring at any places that they have installed and suspected the power supply from the main supply was having a problem.General observation showed that the PC (Personal Computer) commissioning and installation is following the standard procedure.The location of the PC,the humidity and temperature all are within the standard operating condition.The power supply from the main distribution board is protected via a standard circuit breaker and additionally protected via Automatic Voltage Regulator (AVR).Nevertheless,having these protections does not mean that the power supply is safe to be used with any equipment.According to the yearly equipment maintenance report of the faculty,the breakdown of the PC usually on the power supply block of the PC.This symptom can only mean either incoming power supply is giving unsafe power or power supply block’s is not reliable.In this project, the electrical parameters of the incoming power supply will be monitored using the PM1000F with Flicker & Harmonic Distortion measurement meter.Important parameters that are expected to be extracted from this monitoring process are current,voltage,frequency and total harmonic distortion.A backup monitoring equipment will be set up as well as nearby laboratory for references and comparison analysis.Initial monitoring that was done recently showed that during early morning the voltage has dropped about 10%.Even though it is normal,the occurrence of the event may increase the stress to the power supply block.The result or data will be analysed to find out the real problems with the equipment as mentioned by the technician and the vendor.